Characterization of Vibrio cholerae’s Extracellular Nuclease Xds - Pressler, Katharina; Mitterer, Fabian; Vorkapic, Dina; Reidl, Joachim; Oberer, Monika; Schild, Stefan (Frontiers in Microbiology, 2019)
The Gram negative bacterium Vibrio cholerae encodes two nucleases, Dns and Xds, with extracellular activity, which are able to degrade extracellular DNA and play a major role during the human pathogen’s lifecycle. Along the environmental, inter-epidemic persistence of the pathogen, Dns and Xds control three-dimensional biofilm formation and bacterial detachment from biofilms via degradation of extracellular DNA. During intestinal colonization the enzymes facilitates survival fitness mediating evasion from neutrophil extracellular traps, which are part of the innate immune response. However, only Xds degrades extracellular DNA down to nucleotides, which are an important nutrient source for V. cholerae. Thus, Xds is a key enzyme for survival fitness during distinct stages of the V. cholerae lifecycle and could be a potential therapeutic target. This work provides detailed information about the enzymatic properties of Xds using purified protein in combination with a real time nuclease activity assay. The experiments revealed an optimal buffer composition for Xds activity being 50 mM Tris/HCl pH 7, 100 mM NaCl, 10 mM MgCl2 and 20 mM CaCl2, respectively. Moreover, highest Xds activity was observed by using substrate DNA with low GC content and ambient temperatures of 20 to 25°C. Based on in silico analysis and homology modelling, truncated versions and point mutants of Xds were generated to confirm that the C-terminal part harboring a predicted exonuclease domain is sufficient for nuclease activity. In detail, D787 and H837 residues in the predicted exonuclease domain were identified to play a major role in formation of the catalytic center.